Iterative Development of a Web Application to Support Teleconferencing of a Distributed Tumor Board - Li, H (2002)
We have developed a web-based information system to support a distributed tumor conference held in multiple locations via videoconferencing over high-speed Internet connections. The information system stores images, and other objects such as Word documents, PowerPoint presentations, and URLs, which are pertinent to the conference presentations, as well as patient and conference metadata. A web-based interface allows clinicians to directly organize conference data, and display that information during a clinical conference. We implemented the system using open source software. It has been deployed since January 2001, and is the subject of an ongoing iterative development and evaluation process.